Molecular roles of microRNA-21 and exosomal miR-21 in gastrointestinal cancers: diagnostic, therapeutic, and drug resistance insights - Wang, Chunguang; Bai, Meiling; Liu, Xingliang; Li, Zhijun; Wang, Haibin; Guo, Shengbin (Frontiers in Molecular Biosciences, 2025)
MicroRNA-21 (miR-21) and its exosomal variant have gained recognition as pivotal molecular contributors to the etiology and advancement of gastrointestinal (GI) neoplasms, encompassing colorectal, gastric, pancreatic, and esophageal cancers. From a biosciences standpoint, miR-21 operates as a formidable oncomiR by inhibiting tumor suppressor genes, consequently fostering the dysregulated activation of crucial signaling cascades. The exosomal form of miR-21, released through tumor-derived extracellular vesicles, enhances intercellular interactions within the tumor microenvironment, influencing processes such as angiogenesis, immune evasion, epithelial-mesenchymal transition (EMT), and metastasis. Clinically, both tissue and circulating (serum/plasma) concentrations of miR-21 exhibit substantial potential as non-invasive biomarkers for the early detection, disease stratification, and prognostic assessment in gastrointestinal malignancies. Increased levels of exosomal miR-21 are associated with diminished overall survival, lymph node dissemination, and resistance to chemotherapeutic agents such as 5-fluorouracil, cisplatin, and gemcitabine. Mechanistically, exosomal miR-21 facilitates drug resistance by inhibiting apoptotic pathways and promoting cellular longevity through the modulation of the tumor microenvironment and stromal-tumor interactions. Therapeutically, bioscience-oriented strategies aimed at targeting miR-21 are currently under scrutiny to counteract chemoresistance and restore therapeutic effectiveness. These methodologies possess significant potential for applications in personalized medicine concerning gastrointestinal cancers. This review synthesizes contemporary biosciences perspectives on the molecular roles of miR-21 and exosomal miR-21, underscoring their diagnostic, prognostic, and therapeutic significance in gastrointestinal neoplasms. Particular emphasis is directed toward their involvement in overcoming drug resistance, thereby establishing them as promising targets for forthcoming translational oncology investigations.